Dynamic effects and information quantifiers of statistical memoryof MEG's signals at photosensitive epilepsy - R. M. Yulmetyev; E. V. Khusaenova; D. G. Yulmetyeva; P. Hänggi; S. Shimojo; K. Watanabe; J. Bhattacharya (Mathematical Biosciences and Engineering)
The time series analysis of magnetoencephalographic (MEG) signalsis very important both for basic brain research and for medicaldiagnosis and treatment. Here we discuss the crucial role ofstatistical memory effects (ME) in human brain functioning withphotosensitive epilepsy (PSE). We study two independentstatistical memory quantifiers that reflect the dynamicalcharacteristics of neuromagnetic brain responses on a flickeringstimulus of different colored combinations from a group of controlsubjects, which are contrasted with those from a patient with PSE.We analyze the frequency dependence of two memory measures forthe neuromagnetic signals. The strong memory and the accompanyingtransition to a regular and robust regime of the signals' chaoticbehavior in the separate areas are characteristic for a patientwith PSE. This particularly interesting observation most likelyidentifies the regions of the protective mechanism in a humanorganism against occurrence of PSE.